Enantioselective phase transfer catalyzed synthesis of spirocyclic azetidine oxindoles - Boddy,AJ; Sahay,AK; Rivers,EL; White,AJP; Spivey,A; Bull,J (Organic Letters, 2024)
Spiro-3,2’-azetidine oxindoles combine two independently important pharmacophores in an understudied spirocyclic motif that is attractive for medicinal chemistry. Here, the enantioselective synthesis of these structures is achieved in ers of up to 2:98 through intramolecular C–C bond formation, involving activation of the substrate with a novel SF5-containing chiral cation phase transfer (PT) catalyst. The products are readily elaborated/deprotected to afford medicinally relevant enantioen-riched compounds. Control experiments suggest an interfacial PT mechanism, whereby catalytic asymmetric induction is achieved through activation of the chloride leaving group.